Digital age-related disorders: An epidemiological analysis (Research, Society and Development, 2025)
Technological advancement and the excessive use of digital devices have raised concerns related to mental and physical health, especially among children and adolescents. Disorders such as anxiety, depression, insomnia, and digital addiction have become increasingly prevalent, with hyperconnectivity and excessive screen time being significant risk factors. Thus, this study aims to synthesize the main scientific findings on the topic, identifying epidemiological trends, the most vulnerable population groups, and the prevention and intervention strategies described in the literature. Social media addiction, the fear of social exclusion, and the constant search for validation are frequently associated with excessive technology use, affecting young people's behavior and interpersonal relationships. Studies also point to the physical impact of technology, such as sleep disorders and musculoskeletal pain. The World Health Organization recognizes these disorders as public health concerns, including digital addiction and disorders related to video game use. To mitigate these effects, the research highlights the importance of preventive strategies, such as educational campaigns for parents, educators, and adolescents, as well as the regulation of screen exposure time. The narrative review of studies also emphasizes the need for effective public policies and the development of safer and healthier digital spaces. The scarcity of studies in non-Western contexts limits the generalization of results, indicating the need for research in different regions and cultures.